2020
DOI: 10.1111/pcn.13107
|View full text |Cite
|
Sign up to set email alerts
|

Case with psychotic disorder as a clinical presentation of COVID‐19

Abstract: We investigated whether there was an increased interest in quitting smoking in late February, March, and April compared with the preceding weeks. The interest in the search term 'how to quit smoking' showed significant increase on 9 March (90 RSV) and the interest in the search term reached 100 RSV on 19 April (Fig. 1). The interest in the search term 'how to quit alcohol' showed significant increase on 11 February (100 RSV). However, the interest for both the search terms was not stable over the study period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…( 10 ) Although anti-neural autoantibodies are present in some neurologically impaired COVID-19 patients(11-13), autoantibody studies are rarely performed in cases of COVID-19-associated psychosis. ( 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 )…”
Section: Discussionmentioning
confidence: 99%
“…( 10 ) Although anti-neural autoantibodies are present in some neurologically impaired COVID-19 patients(11-13), autoantibody studies are rarely performed in cases of COVID-19-associated psychosis. ( 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 )…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table 1 available at provides a summary of characteristics of the included studies in this review. 2,4-50…”
Section: Resultsmentioning
confidence: 99%
“…21,22 There were three case reports with new-onset non-reactive psychosis: one in a patient self-medicated with chloroquine; 23 one in a patient who had been recently admitted to hospital for COVID-19 infection and received treatment including hydroxychloroquine and prednisone; 30 and one in a patient who was admitted for COVID-19 infection and developed psychosis requiring a second admission to the hospital. 31 Three studies reported a relapse of psychosis triggered by the stress of the pandemic 35,36 or quarantine. 37 In one of these cases, the patient had incorporated COVID-19 into their delusional system, and developed symptomatic COVID-19 infection during their hospital stay; 36 and in another case, the patient was found to have a positive COVID-19 test result.…”
Section: Resultsmentioning
confidence: 99%
“…The response to the pandemic described here will surely change, and thus research will need to continue to evaluate it. The COVID-19 pandemic has been a challenge for clinicians, due to new clinical presentations ( Majadas et al, 2020 ) and new treatment approaches. Research should continue to study the impact of COVID-19 on drug dependence and its treatment.…”
Section: Discussionmentioning
confidence: 99%